STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA KARYAWAN - Anggia Ramadhan (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
This study aims to identify and analyze the first strategy of human resource management in improving the performance of employees of PT Pelabuhan Indonesia 1 (Persero) North Sumatra. Second, to find out the results of the SWOT analysis of the strategy for improving employee performance with the IFAS and EFAS matrices, it is possible to identify important factors from both the external and internal environment which are the strengths, weaknesses, opportunities and threats of improving performance. The research approach carried out in this study is descriptive qualitative, the author also uses SWOT analysis. SWOT analysis is the identification of various factors systematically to formulate corporate strategy. From the results of the analysis obtained a growth strategy or growth oriented strategy, this strategy indicates a strong company condition and is able to continue to grow by taking the opportunities and opportunities that exist to achieve maximum turnover. This strategy was chosen because the calculation results are in quadrant I where the total weighted score for strengths and weaknesses is 2.710504 while the total weighted score for opportunities is 2.653142. The position in this quadrant is very profitable and can be applied to the maximum.